As relações entre natureza e convenção em Antifonte e no Anônimo de Jâmblico - Fabrício Soares Santos Fontes (2016)
This thesis aims to explore the concepts of physis (nature) and nomos (custom, law, convention) and the theories associated with them by Antiphon and the Anonymous Iamblichus. Due to the issues involving the identities of these two philosophers, we start by making a brief introduction on the sources of available fragments and the opinions of scholars concerning them. In the central part of the text, we confront Antiphon and the Anonymous on the relations between law and nature, especially the impact these factors have on the life of the individual and on the city. We try to demonstrate that Antiphon does not merely make opposition to the law, but is critical of it and of certain conceptions of justice. We investigate the circumstances in which and the criteria according to which Antiphon recommends that one should follow nature instead of law, whenever they oppose each other. We show a probable link between the thought of the Anonymous and that of Protagoras, especially in what concerns the natural necessity of laws, and confront it with theses attributed to Thrasymachus and Callicles in Plato´s dialogues. We counter Antiphon´s criticism to laws and customs with the praise made of them by the Anonymous, as well as the opposition between law and nature in Antiphon with the need of laws, as a kind of imposition by nature in the Anonymous and in Protagoras.Finally, we also investigate the role of education in the raising of humans and their relation to nature, confronting the thesis of natural equality, sustained by Antiphon, with the one concerning the variations of natural aptitude referred to by the Anonymous, as well as the way in which natural factors interact with controlled factors in the acquisiton of excellence.